2017
DOI: 10.3389/fnhum.2017.00244
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Modulations of N170 Component during Emotional Processing and Their Links to Social Behaviors in Ex-combatants

Abstract: Emotional processing (EP) is crucial for the elaboration and implementation of adaptive social strategies. EP is also necessary for the expression of social cognition and behavior (SCB) patterns. It is well-known that war contexts induce socio-emotional atypical functioning, in particular for those who participate in combats. Thus, ex-combatants represent an ideal non-clinical population to explore EP modulation and to evaluate its relation with SCB. The aim of this study was to explore EP and its relation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
(105 reference statements)
0
11
0
Order By: Relevance
“…Conflicting N170 results exist as a function of traumatic experiences. Although childhood trauma is linked to smaller N170 amplitude to angry/fearful as opposed to happy faces (83, 85), both combat-related trauma and PTSD+ are associated with heightened N170 amplitudes to faces more generally (84) but no N170 amplitude change to angry faces as a function of pre- versus post-deployment in PTSD+ and PTSD− with similar combat trauma (65). The P2 literature is equally messy in that PTSD+ display either attenuated P2 amplitude to happy faces (66, 121) but enhanced P2 amplitude to various faces when compared to PTSD− with traumatic brain injury (TBI) (123).…”
Section: Event Related Potential Markers Of Trauma Experience and Posmentioning
confidence: 99%
“…Conflicting N170 results exist as a function of traumatic experiences. Although childhood trauma is linked to smaller N170 amplitude to angry/fearful as opposed to happy faces (83, 85), both combat-related trauma and PTSD+ are associated with heightened N170 amplitudes to faces more generally (84) but no N170 amplitude change to angry faces as a function of pre- versus post-deployment in PTSD+ and PTSD− with similar combat trauma (65). The P2 literature is equally messy in that PTSD+ display either attenuated P2 amplitude to happy faces (66, 121) but enhanced P2 amplitude to various faces when compared to PTSD− with traumatic brain injury (TBI) (123).…”
Section: Event Related Potential Markers Of Trauma Experience and Posmentioning
confidence: 99%
“…In a previous study with Colombian ex-combatants, we observed atypical behavioural and electrophysiological EP markers associated to imprecise valence attribution for faces, words, and ecological images (Quintero-Zea et al, 2017;Tobón et al, 2015;Trujillo, Valencia, et al, 2017). Additionally, we described a differential neural pattern represented by the modulation of the N170 component during EP; i.e., ex-combatants privilege face processing over verbal content as a potential neural strategy to improve the recognition of meaningful social information provided by their environment (Trujillo, Valencia, et al, 2017). Furthermore, larger amplitude in the LPP component related to the recognition of valence in contextual emotional images and its association to lower emphatic personal distress dimension have also been informed (Tobón et al, 2015).…”
Section: Introductionmentioning
confidence: 78%
“…Combat experience is often associated to stress-induced cognitive atypical functioning and to an increase of mental health risks, such as lower quality of life perception and higher prevalence of mental disorders (Castro, Adler, McGurk, & Bliese, 2012;Godfrey et al, 2015;Weierstall, Castellanos, Neuner, & Elbert, 2013). Furthermore, diminished empathic disposition (Tobón et al, 2015;Trujillo, Trujillo, Ugarriza, et al, 2017), increase among aggressive attitude and violence (Gallaway, Fink, Millikan, & Bell, 2012;Godfrey et al, 2015;Tobón et al, 2016), and antisocial behaviour (Kaplan & Nussio, 2013) have also been informed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurocognitive modulations linked to chronic exposure to war/armed conflict experiences makes heavy demands upon emotional processing for the elaboration and implementation of adaptive social strategies in situations fraught with fatal risk. Ex-combatants, from illegally armed groups in Colombia, presented with higher assertion skills and showed more pronounced brain responses to faces than the control group, without combat experience, lacking also the bias toward "anger" that was observed in the control group wherein the latter group showed a greater likelihood of misclassifying the "neutral" faces as "angry" [6].…”
Section: Introductionmentioning
confidence: 88%